SHADOW BANKING IN CENTRAL AND EASTERN EUROPE: SPECIFICITIES AND DRIVERS (The South East European Journal of Economics and Business, 2024)
he paper analyses the specificities and drivers of the shadow banking (SB) system in eleven Central and Eastern European (CEE) EU member states for 2004-2019. It contributes to the understanding of the CEE SB in terms of how the structural features of the financial and banking system determine its development. The SB system of the region is much smaller, and its structure is less complex and significantly different from that of developed European countries: the role of capital market intermediaries is smaller, while the role of nonbank lenders is larger. Specific features of the CEE financial system include the dominance of banks, the relative underdevelopment of capital markets, the dominance of foreign ownership, and, until the mid-2010s, the reliance on foreign interbank funding in several countries. Indeed, as the results of our panel regression show, regional specificities in the structural characteristics of financial systems are key for the development of the SB.